Recent Advances in Biomedical Applications of Biogenic Nanomaterials - Bhagat, Devidas S.; Gurnule, Wasudeo B.; Bumbrah, Gurvinder S.; Koinkar, Pankaj; Chawla, Pooja A. (Current Pharmaceutical Biotechnology, 2023)
The synthesis of biogenic nanoparticles from readily available natural resources may have large demand in numerous fields including pharmaceuticals and medicine. The biogenic nanoparticles catch the attention of the scientific community due to their low cytotoxicity and biocompatibility. Chemical, physical, and greener methods are used for the synthesis of biogenic nanoparticles. Researchers used eco-friendly and nontoxic approaches in the synthesis of this nanoparticle. This nanomaterial-based medicine plays a vital role in the management of public health, including earlier detection of disease, therapeutics candidates in the treatment of cancer. Biogenic nanocomposites are environmentally benign candidates that include fabrication of various composites, detoxification, and act as a catalyst in the biodegradation process. In this review article, we emphasize the recently reported methods used for synthesis, summarizing their biomedical applications and commercial and environmentally benign applications. Synthetic strategies include greener, chemical, physical, and biogenic methods and their role in surface modifiers involves various biomedical, commercial, and environmental-related applications. Moreover, we glimpse existing status, key contests, and future perspectives.
Keywords: biosynthesis